Tradition of “bobaso se rasai”: Building religious moderation from the heart - Amir Tomagola (12 Waiheru, 2022)
The main purpose of the study is to comprehensively describe local tradition of “Bobaso Se Rasai”. Bobaso Se Rasai tradition is a sacred practice presented in the seven values of humanity in Ternate Sultanate that has become traditional community principle to live contiguously, and to socialize with others in affection, compassion, and respectability in order to maintain the harmony and serenity in society. It is believed that this tradition is the practice of the forefathers of Ternate Sultanate that prioritises humanity, differences respecting, and peace loving to prevent conflict and chaos in North Maluku. Hence, the religion moderation concept and Bobaso Se Rasai tradition can complement one another to build solidarity in the region.